2015 IEEE International Advance Computing Conference (IACC) 2015
DOI: 10.1109/iadcc.2015.7154894
|View full text |Cite
|
Sign up to set email alerts
|

Parameters tuning of OLSR routing protocol with metaheuristic algorithm for VANET

Abstract: Vehicular Adhoc Network provides ability to wirelessly communicate between vehicles. Network fragmentations and frequent topology changes (Mobility of the nodes) and limited coverage of Wi-Fi, are issues in VANET, that arise due to absence of central manager entity. Because of these reasons, routing the packets within the network is difficult task. Hence, provisioning an adept routing strategy is vital for the deployment of VANETs. The optimized link state routing is a well-known mobile adhoc network routing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These frameworks can be classified to mono‐objective or multi‐objective optimisation‐based frameworks. In the mono‐objective optimisation‐based frameworks, the parameter optimisation problem is converted into a mono‐objective problem by calculating the fitness function as a formula of the different objectives [10–16]. Alternatively, a multi‐objective optimisation algorithm considers different conflicting objectives and produces a set of Pareto optimal solutions that can be exploited to select the preferable trade‐off [5].…”
Section: Related Workmentioning
confidence: 99%
“…These frameworks can be classified to mono‐objective or multi‐objective optimisation‐based frameworks. In the mono‐objective optimisation‐based frameworks, the parameter optimisation problem is converted into a mono‐objective problem by calculating the fitness function as a formula of the different objectives [10–16]. Alternatively, a multi‐objective optimisation algorithm considers different conflicting objectives and produces a set of Pareto optimal solutions that can be exploited to select the preferable trade‐off [5].…”
Section: Related Workmentioning
confidence: 99%
“…Dynamic choice mechanism is used by LDSR protocol in order to constraint query to a small region and full flooding localization which is based on original DSR protocol and constrained by two factors: (1) the small-world theory determines the maximum number of hops of query localization flooding ; (2) mobile critical transmitting range determines the effective routing time for connectivity in Ad Hoc network and the maximum mobile speed of node. simulation results have shown that LDSR protocol can produce better average end-to-end delay ,but packet delivery fraction decreased as compared to DSR protocol Anusha bandi and Chandrashekhar [7]have proposed an optimization strategy in order to fine-tune few metrics like delay, packet delivery ratio by enhancing the OLSR protocol with the help of particle swarm optimization. The few metrics has been taken into account in order to compare the values of fitness,packet delivery ratio and throughput.In the end particle swarm optimization algorithm has been compared with genetic algorithm by taking into account QoS parameters.…”
Section: B Optimized Routing Algorithmsmentioning
confidence: 99%